Strategi Manjemen Sumber Daya Manusia Dalam Meningkatkan Kinerja Pegawai Upi Zero Waste Kabupaten Tulungagung - Amilin, Luluk; Jatmiko, Udik (Otonomi, 2024)
This research aims to analyze the human resource management (HRM) strategy implemented in improving employee performance at UPI Zero Waste, Tulungagung Regency. The main focus of the research is evaluating the effectiveness of HRM policies and their impact on employee satisfaction, participation, efficiency and effectiveness of performance. The research method used is a qualitative and quantitative approach by conducting interviews, observation and quantitative data analysis. The research results show that the implementation of HRM policies contributes positively to employee satisfaction, which is reflected in their active participation in employee development programs. Performance efficiency and effectiveness have also increased as a result of a well-planned HRM strategy. Apart from that, good performance management and giving appropriate rewards are important factors in encouraging employee motivation. This research provides a comprehensive picture of effective HRM strategies in improving employee performance at UPI Zero Waste. The implications of these findings can provide a basis for similar organizations to improve and optimize HRM policies to achieve higher and sustainable performance goals.